(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This study proposes a behavior analytic interpretation of constructs of Developmental Psychology regarding parental behavior and their relationships with the developmental characteristics of babies, pre-school children, school-age children and teenagers. The concept of sensitive responsiveness is articulated with the concept of triple contingency and with the notions of effect of pleasure and effect of strengthening of reinforcement contingencies. Pre-school and school children behavior problems and their relationships with parental care are discussed, with emphasis on the analysis of the functions of complaints regarding child behavior. This can be enhanced by adopting the concept of parental educational social skills. The typology of parenting styles is interpreted from a behaviorist perspective, considering the behavioral standards of each style and their impact on the development of adolescents. Parental sensitivity to prevailing contingencies in parent-child interaction appears to stand out as a crucial aspect in the three stages of development that were examined.